The Social Function Of Imi’s In The Exemption Of Micro Business Loans - Hanif Fadlillah, Sri Herianingrum, Fitri Drasmawita, Ririn Tri Ratnasari, (Opción, 2019)
The aim of this study is to determine the role of IMI institutions in the release of customers from money lenders via qualitative methods. Thus the role of IMI in its financing products has an influence on improving the welfare of people who have financial constraints and can help alleviate people’s debts to moneylenders. In conclusion, IMI has succeeded in gathering Islamic social funds in the form zakat, infaq, shadaqoh and waqf (ZISWAQ). These funds are used intensively by IMI to help micro-businesses that experience economic difficulties, especially in the interest of non-stop interest debt.